2021
DOI: 10.1021/acsomega.0c04810
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reduces Cognitive Deficits by Inhibiting Neuroinflammation through the Endoplasmic Reticulum Stress Pathway in Apolipoprotein E4 Transgenic Mice

Abstract: Apolipoprotein E4 (ApoE4) is the main genetic risk factor for Alzheimer’s disease (AD), but the exact way in which it causes AD remains unclear. Curcumin is considered to have good therapeutic potential for AD, but its mechanism has not been clarified. This study aims to observe the effect of curcumin on ApoE4 transgenic mice and explore its possible molecular mechanism. Eight-month-old ApoE4 transgenic mice were intraperitoneally injected with curcumin for 3 weeks, and the Morris water maze test was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…The mice were exposed to alternating light for 12 h, and they could obtain food and water freely. The experiment was carried out in accordance with the Guideline for Care and Use of Laboratory Animals published by the US National Institutes of Health, and the Guidelines for the ethical review of laboratory animal welfare People’s Republic of China National Standard GB/T 35892-2018 [ 39 ], and it was approved by the Ethics and Animal Care and Use Committee of Henan University (approval No. HUSOM-2020-389).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were exposed to alternating light for 12 h, and they could obtain food and water freely. The experiment was carried out in accordance with the Guideline for Care and Use of Laboratory Animals published by the US National Institutes of Health, and the Guidelines for the ethical review of laboratory animal welfare People’s Republic of China National Standard GB/T 35892-2018 [ 39 ], and it was approved by the Ethics and Animal Care and Use Committee of Henan University (approval No. HUSOM-2020-389).…”
Section: Methodsmentioning
confidence: 99%
“…ApoE4 is the major genetic risk factor for AD associated with dementia. Kou et al (2021) found that ApoE4 transgenic mice had impaired cognitive capacity, which is linked to ER stress and activation of inflammatory signaling in the nervous system; these were reversed by curcumin treatment in AD mice. Curcumin is also found effective in Pelizaeus-Merzbacher disease of mice model (Gow et al, 1998;Hübner et al, 2005;Yu et al, 2012).…”
Section: Mutation Associated Neuropathiesmentioning
confidence: 99%
“…Curcumin also reduce Aβ levels by delaying APP maturation in the secretory route (Zhang et al, 2010). The anti-inflammatory properties of curcumin have been linked to improved learning and memory in ApoE4 mice (Kou et al, 2021).…”
Section: Curcumin and Neurodegenerative Diseases: Interventions And Modalitiesmentioning
confidence: 99%
“…Likewise, administering curcumin via peripheral injections crossed the blood–brain barrier and decreased plaque levels and blocked subsequent plaque development [ 152 ]. Furthermore, various studies using animal models of AD have demonstrated enhanced cognitive function in curcumin-treated groups, potentially due to curcumin’s ability to decrease the levels of Aβ plaques, as well as its antioxidant and anti-inflammatory properties [ 154 , 155 ]. To illustrate this, a double-transgenic APP/PS1 AD model allowed researchers to inspect the effects of two different curcumin dosages, including a 160 ppm low dose and 1000 ppm high dose for a period of 6 months [ 156 ].…”
Section: Herbal Neuroprotective Effectsmentioning
confidence: 99%